Pemanfaatan Limbah Ekstrak Metanol Dari Kulit Buah Kakao (Theobroma Cacao L.) Sebagai Antimikroba - Mierza, Vriezka; Razali, Mariany; Hanafi, Muhammad; Pandiangan, Martina (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Microorganisms, which include bacteria, fungi, viruses, and parasites, are a large class of microscopic organisms with one or more cells. Among them are Staphylococcus epidermidis, Bacillus subtilis, Proteus mirabilis, and Streptococcus pyognes. One type of plant that has health benefits is the cocoa plant (Theobroma cacao L.) which belongs to the Malvaceae tribe. In this study, methanol extract of cocoa fruit peel (Theobroma cacao L.) was made as an inhibition test against Streptococcus pyognes, Bacillus subtilis, Proteus mirabilis, and Staphylococcus epidermidis bacteria. Cocoa pod peel (Theobroma cacao L.) was the test material used in the experimental methodology of this study. Simplisia preparation, ethanol solvent maceration extraction, agar diffusion method antibacterial activity testing, and phytochemical screening for chemical compound component analysis are part of the stages of this research. Drying of cocoa fruit peels produced 26.5 kg of simplisia, and maceration with ethanol produced 14.41 g of thick extract. Antibacterial activity of ethanol macerated extract of cocoa fruit peel was shown by inhibition against Streptococcus pyognes bacteria by 21 mm, Bacillus subtilis bacteria by 68 mm, Bacillus subtilis bacteria by 14.06 mm, Proteus mirabilis bacteria by 14.4 mm, and Staphylococcus epidermidis bacteria at a concentration of 100 mg/ml. The results of phytochemical screening of ethanol extract of cocoa pod skin showed the presence of anthraquinone glycosides, flavonoid chemical compounds, triterpenoids, tannins, and saponins.